COLLABORATIVE NETWORKS, HISTORICAL-CONCEPTUAL REVIEW AND THE “WE” TEACHERS IN BRAZIL’S STRICT SENSU - Schmitt, Adriana Regina Vettorazzi; Pacheco, Luci Mary Duso (Revista Literatura em Debate, 2025)
This article presents a historical and conceptual review of collaborative networks in science, focusing on the role of teachers, researchers, and advisors—who serve as the "nodes" of academic intellectual production that have driven intellectual and scientific output in graduate education (stricto sensu) in Brazil over the past 20 years. The study is based on bibliographic and documentary research with a qualitative approach, and data are analyzed using the Discursive Textual Analysis (DTA) technique. Collaboration in science emerged from the efforts of artisans and apprentices to share their knowledge and creations. Later, it became a way to draw the attention of scientists and humanists to a routine yet often overlooked aspect of scientific production: collaboration as both a technique and a humanistic dimension of knowledge creation. Scientific networks are sustained by the strength of educators [nodes] who challenge their students [edges] to explore this theme, fostering the development of collective competencies to solve problems across various fields of knowledge.